Filósofos en 90 minutos. (Pack 2), (Hegel, Nietzsche, Locke, Schopenhauer, Marx y Kant) - Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940-; Strathern, Paul, 1940- (Tres Cantos, Madrid, España : Siglo XXI de España Editores, S.A., 2017)
The Pack Filósofos 2 collection brings together 6 of the most outstanding philosophers of the 17th-19th centuries.
Hegel en 90 minutos -- Nietzsche en 90 minutos -- Locke en 90 minutos -- Schopenhauer en 90 minutos -- Marx en 90 minutos -- Kant en 90 minutos.
This collection of books by Strathern were published separately in print. The publisher now combined them by subject and published them together in digital format.
Includes bibliographical references.
Online resource; title from ePub title page (Digitalia, viewed February 7, 2019)
Keywords: Nietzsche, Friedrich Wilhelm, -- 1844-1900.; Schopenhauer, Arthur, -- 1788-1860.; Marx, Karl, -- 1818-1883.; Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Kant, Immanuel, -- 1724-1804.; Locke, John, -- 1632-1704.; Philosophers -- Biography; Biographies; Electronic books